2017
DOI: 10.18793/lcj2017.21.06
|View full text |Cite
|
Sign up to set email alerts
|

‘Heat-Smart’ schools during physical education (PE) activities: Developing a policy to protect students from extreme heat

Abstract: National and state surveys of school sun protection policies and practices demonstrate that being a member of a SunSmart Program improves sun protection practices in primary schools, often lead by Health and Physical Education (HPE) teachers. Australia's major Sunsmart program implemented in primary schools has largely focused on limiting children's exposure to ultraviolet radiation (UVR) to reduce the risk of developing skin cancer later in life. Yet another major hazard during outdoor physical education acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The influences of heat and whether there were enough resources to protect primary school students against extreme weather was noted as perceived barriers. In very hot climates, environmental heat can negatively influence engagement in outdoor PE activities via heat stress (Hyndman, 2017b) which can cause children to appear 'listless' or 'restless', complain about the heat/humidity and voice negative feelings about physical activity throughout a school year from heat stress (Doecke, 1992). Similar to the extremes of heat, cooler weather can negatively impact on school children's physical activity participation (Hyndman, Chancellor, & Lester, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The influences of heat and whether there were enough resources to protect primary school students against extreme weather was noted as perceived barriers. In very hot climates, environmental heat can negatively influence engagement in outdoor PE activities via heat stress (Hyndman, 2017b) which can cause children to appear 'listless' or 'restless', complain about the heat/humidity and voice negative feelings about physical activity throughout a school year from heat stress (Doecke, 1992). Similar to the extremes of heat, cooler weather can negatively impact on school children's physical activity participation (Hyndman, Chancellor, & Lester, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The second element of appropriateness includes unsafe sun exposure (American Academy of Pediatrics, American Public Health Association, & National Resource Center for Health and Safety in Child Care, 2011). Research has shown modern playground materials, along with extreme hot temperature peak periods (e.g., 10 a.m.-2 p.m.), can expose students to unsafe circumstances (Hyndman, 2017). In addition, the type of playground surfacing materials under playground equipment plays a role in the playground environment's temperature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3). [47] Few interventional studies have addressed this topic, however. In one study in Costa Rica, learning outcomes improved after air conditioning was installed in the classrooms.…”
Section: Interventions To Reduce Heat Stress In Schoolsmentioning
confidence: 99%